Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen di Pencucian Mobil dan Motor LMC 338 - Risdawanty Risdawanty; Lati Sari Dewi (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to find out the quality of service, consumer satisfaction and how much the influence of service quality on consumer satisfaction in LMC 338 car and motorcycle wash. The research method used is quantitative descriptive and the nature of the research is reflexive. The sampling method used the incidental sampling method, the sample determination used the lemeshow formula with a 95% accuracy rate and the sample in this study amounted to 96 people. The data analysis used was a simple linear regression analysis with the help of IBM SPSS v. 27.0 software. The results of the study show that the quality of service measured by the Likert scale is very good, consumer satisfaction is very good and based on the results of the T test that has been carried out, the quality of service has a significant effect on consumer satisfaction at LMC 338 car and motorcycle washes.